TYPES OF DIRECTIVE SPEECH ACT FOUND IN ABOMINABLE FILM - Saidi, Alvien Adham Rizkyanto; Candra, Komang Dian Puspita; Skolastika, I Made Perdana (LITERA : Jurnal Bahasa Dan Sastra, 2023)
This study aims to find out the types of directive speech act occur in the Abominable film. As the result from the felicity condition on their utterance that makes the writer interesting to analyze because often occurs in daily life. Three data were collect and analyzed the findins of the data by used descriptive qualitative as methods. In analyzed data, the theory used proposed by Searle (1979) to analyze the types of directive speech act. In taking the data in this study, observation methods and note-taking techniques were used. Data findings are presented in formal and informal methods. Formal methods are presented in the form of percentages tables, while informal methods are presented in the form of descriptive writing in explained the table. The result of this study shows there are 3 utterances were found contained directives namely asking act, telling act, and requesting act.